Ekspresi HER-2/neu dan Ki-67 pada Karsinogenesis Endometrium - Febrina Diah Puspitasari; Faroek Hoesin; Dyah Fauziah (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2014)
Background Endometrial cancer is the most prevalent gynecological cancer in the Western World. In Dr. Soetomo Hospital, endometrial carcinoma is the second commonest cancer affecting women. HER-2/neu is a receptor on the cell surface which activate cellular proliferation. Ki-67 protein is present in the nucleus of cells that are actively undergoing proliferation. The role of HER-2/neu and Ki-67 overexpression in carcinogenesis of endometrial carcinoma is not clear. This study is to determine the difference of HER-2/neu and Ki-67 expression in normal endometrium, simple hyperplasia without atypia, and endometrial carcinoma endometrioid. Methods This study used cross sectional design. Samples were retrieved from Pathology archives at Dr. Soetomo Hospital during January 2011-December 2011. Normal endometrium in proliferation phase, simple hyperplasia without atypia, and endometrial carcinoma endometrioid were collected and stained with immunohistochemistry using HER-2/neu and Ki-67. Statistical analysis with Kruskal-Wallis and Mann Whitney were performed. Result There were 9 samples with glandular proliferation, 18 samples with simple hyperplasia without atypia, and 18 samples with endometrial carcinoma endometrioid type. Statistical analysis showed no significant difference of HER-2/neu expression in proliferation phase, simple hyperplasia without atypia, and endometrial carcinoma endometrioid (p=0.054) but Ki-67 expression had significant difference in proliferation phase, simple hyperplasia without atypia, and endometrial carcinoma endometrioid (p=0.001). Conclusion There was not significant difference in HER-2/neu expression but significant difference in Ki-67 expression on glandular proliferation, simple hyperplasia without atypia, and endometrial carcinoma endometrioid. Key words : endometrioid, endometrium, HER-2/neu, Ki-67, simple hyperplasia without atypia.